Use of fly ash in black cotton soil for road construction - Hardaha, Rajendra Prasad; Agrawal, M L; Agrawal, Anita (Recent Research in Science and Technology, 2013)
<span style="font-size: 10.0pt; line-height: 115%; font-family: "Arial Narrow","sans-serif"; mso-fareast-font-family: BatangChe; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 1.0pt; mso-fareast-language: KO; mso-bidi-font-weight: bold;">Waste products from various industries normally deposited in landfills, have been proposed for use as an alternate construction material. The utilization of these alternate materials needs to be encouraged for economy of construction and conservation of materials. One by-product that has shown as an alternate construction material is fly ash. In this paper an effort is made to use fly ash to stabilise soils for road construction, in order to reduce the amount of waste globally. In the present assignment, black cotton soils were stabilized with different quantities of fly ash. On the basis of preliminary investigations, it has been found that stabilization with fly ash, improves the CBR and plasticity characteristics of black cotton soils.For hydration of fly ash, the lime content is responsible, so substantial improvements in desired properties can be achieved by addition of small quantity of lime. <!--EndFragment--> ie2< rØ‡F `oF Microbiologists have come up with an important point that if genetic modification is carried out extensively, new viruses with greater potential to harm mankind may evolve anytime, and the probability of this occurring can be quite high. This form of dangerous biotechnology will only benefit largely towards the GM crop farmers in form of monetary gain. According to relevant statistics, farmers would save more than US$3.3 billion annually on herbicides, insecticides, and fungicides. So come to think of it. Is it worthwhile to become the guinea pigs just to save a few bucks, while those farmers are sitting down there counting their huge earnings without inflicting any risks on themselves? While some countries have banned GMOs or placed a moratorium on their release, others are increasing both investment levels and land area devoted to cultivating genetically modified (GM) crops. In 2006, GM crops were grown commercially by 10.3 million farmers (9.3 million resource-poor small farmers in developing countries) in 22 countries, on 102 million hectares - about 4 per cent of total arable land worldwide [5]